2017
DOI: 10.1140/epjc/s10052-017-5001-8
|View full text |Cite
|
Sign up to set email alerts
|

COSMOS- $$e'$$ e ′ -soft Higgsotic attractors

Abstract: In this work, we have developed an elegant algorithm to study the cosmological consequences from a huge class of quantum field theories (i.e. superstring theory, supergravity, extra dimensional theory, modified gravity, etc.), which are equivalently described by soft attractors in the effective field theory framework. In this description we have restricted our analysis for two scalar fields -dilaton and Higgsotic fields minimally coupled with Einstein gravity, which can be generalized for any arbitrary number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 235 publications
(287 reference statements)
2
16
0
Order By: Relevance
“…Optical studies on bulk STO (van Mechelen et al 2010) have not only confirmed the involvement of the LO3 phonon in EPI but also found the corresponding effective mass renormalization m*/m 0 ~3.0 close to our value. The same phonon was observed by Raman (Cardona 1965) and neutron spectroscopy (Choudhury et al 2008) as well as by VUV-ARPES at the bare STO(001) surface (Chang et al 2010;Wang et al 2016) with the strength of the polaronic structure depending on n s (see Chapter 4). The LO3 energy ~100 meV found in all these experiments perfectly matches the DFT calculations, Fig, 13 (a).…”
Section: Low Temperature Limitsupporting
confidence: 62%
“…Optical studies on bulk STO (van Mechelen et al 2010) have not only confirmed the involvement of the LO3 phonon in EPI but also found the corresponding effective mass renormalization m*/m 0 ~3.0 close to our value. The same phonon was observed by Raman (Cardona 1965) and neutron spectroscopy (Choudhury et al 2008) as well as by VUV-ARPES at the bare STO(001) surface (Chang et al 2010;Wang et al 2016) with the strength of the polaronic structure depending on n s (see Chapter 4). The LO3 energy ~100 meV found in all these experiments perfectly matches the DFT calculations, Fig, 13 (a).…”
Section: Low Temperature Limitsupporting
confidence: 62%
“…The band is flat with only a small momentum transfer to electrons. This identification is supported by the earlier ARPES on STO surface states, which shows a phonon-induced hump at approximately 100meV away from the main band and through inelastic neutron scattering 8 . The role of substrate in assisting superconductivity is not limited to generation of phonons.…”
Section: Introductionsupporting
confidence: 64%
“…The single phonon band 8,13 near Ω = 100meV is most probably associated with pairing attractive electron-electron force is the ferroelectric LO that involves the relative displacement of the T i and O atoms. The high energy STO oxygen LO phonon band mode is separated from all the other phonon bands by a substantial energy gap 8 . The single branch of the optical phonons described by the bosonic field 22…”
Section: B Phonons and Electron-phonon Interactionsmentioning
confidence: 99%
“…We approximate the relevant phonon branch with a dispersionless Ω q = Ω = 100 meV optical oxygen phonon mode. This is supported by several ab initio calculations that indicate that the highest lying phonon branch in bulk STO [41] and FeSe/STO interfaces [42,43] is relatively flat in the vicinity of q = 0. The e-ph matrix element is taken to depend on the momentum transfer only, as derived microscopically in previous works [11,14].…”
Section: Model Hamiltonianmentioning
confidence: 55%